Prevalence and Risk Factors of Limited Musculoskeletal Health Literacy in the Outpatient Setting: A Logistic Regression Model. Issue 10 (15th May 2019) - Noback, Peter C.; Seetharaman, Mani; Tantigate, Direk; Strauch, Robert J.; Rosenwasser, Melvin P.; Vosseller, J. Turner
Abstract : Introduction: The purpose of this study was to determine the risk factors of limited musculoskeletal health literacy (MHL) in a general population of orthopaedic patients. Methods: Patients presenting to either a foot or ankle surgeon or hand or wrist surgeon were given the Literacy in Musculoskeletal Problems (LiMP) questionnaire, a nine-item survey for assessing "limited" MHL (LiMP score < 6). After confirming group homogeneity, the two populations were analyzed together to determine factors significantly correlated with and predictive of limited MHL. Results: Overall, 231 patients were included in the analysis. Average LiMP score was 5.4 ± 1.8, and 49% of participants had "limited" MHL. Chi-square analysis revealed that being non-Caucasian, using cigarettes, and having a less than college-level education were associated with a higher prevalence of "limited" MHL ( P < 0.05). Logistic regression revealed that being of non-Caucasian race ( P = 0.04) or having less than college-level education ( P = 0.03) were significant independent predictors of "limited" MHL, with adjusted relative risks of 1.37 and 1.40, respectively. Discussion: In this study, the patients at the greatest risk of limited MHL are often at the risk of many other complications. These results should be used as a groundwork to craft directives aimed at improving MHL and outcomes in these patients.